Indian Government and politics - Parkash Chander (New Delhi, 1984)
The book on Indian Government and politics has been designed to meet requirements of the students. The book has been divided into three parts. Part I deals with the features of the Indian Political System in its historical context. Part II deals with the Constituent Assembly and its working.Part III deals with extra-constituent factors which have affected the working and sometimes even strained the existence of the Indian political system.
Keywords: Nationalism India .